Shuujosi Danseigo dalam Game Visual Novel STEINS; GATE - Ramadhani Ramadhani; Maulluddul Haq (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This study aims to describe the variations and functions of shuujoshi danseigo in visual novel games with title STEINS; GATE. This study used qualitative descriptive approach. The data in this study are every speech that uses shuujoshi danseigo, along with speech action information that can explain the context, gestures or behavior of the subject. The source of data for this study is a visual novel game with the title STEINS; GATE. Data collection in this study used SBLC techniques, record techniques, and write techniques. This study uses Chino's theory as a reference and other additional theories as support in classifying and analyzing the functions of each shuujoshi variant. In this study, 94 data sample of shuujoshi danseigo were found, and 7 shuujoshi variants were identified and classified based on Chino's theory. The 7 shuujoshi variants are: shuujoshi dayo, kana, na, sa, yone, ze, and zo. From the 7 variants of shuujoshi danseigo that found, 18 shuujoshi functions in Chino theory can be identified and the examples of their usage is found in the visual novel game STEINS; GATE.